Ukraine on Fire - Muir, Iain (Scotland Today online, 2022)
Ukraine. Across its eastern border is Russia and to its west, Europe. For centuries, it has been at the centre of a tug-of-war between powers seeking to control its rich lands and access to the Black Sea.
Keywords: Oliver Stone; scotland